1987
DOI: 10.1073/pnas.84.10.3467
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic phosphatidylinositol modulation of inhibitory, G protein-linked neurotransmitter actions: electrophysiological studies in rat hippocampus.

Abstract: In electrophysiological studies using the rat hippocampal slice preparation, cholinergic agonists and phorbol 12,13-diacetate, a stimulator ofprotein kinase C, block the inhibitory actions of baclofen, a -aminobutyric acid B receptor agonist, and adenosine. Relative potencies of cholinergic agonists in stimulating the phosphatidylinositol system, as measured biochemically, parallel their activity in blocking adenosine assessed electrophysiologically. Electrical stimulation ofcholinergic afferents also reverses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 39 publications
3
23
1
Order By: Relevance
“…A G protein serves as a substrate for PKC phosphorylation in platelets; the G protein regulating Z,, in brain may be a substrate for PKC, or, conversely, PKC may be regulated by a G protein. Interestingly, phorbol esters, and muscarinic agonists that cause PI turnover, block the ability of adenosine to activate a K conductance in hippocampal neurons (Worley et al, 1987) and oocytes (Dascal et al, 1985). An adenosine-induced increase in K conductance is also mediated by a G protein (Trussel and Jackson, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A G protein serves as a substrate for PKC phosphorylation in platelets; the G protein regulating Z,, in brain may be a substrate for PKC, or, conversely, PKC may be regulated by a G protein. Interestingly, phorbol esters, and muscarinic agonists that cause PI turnover, block the ability of adenosine to activate a K conductance in hippocampal neurons (Worley et al, 1987) and oocytes (Dascal et al, 1985). An adenosine-induced increase in K conductance is also mediated by a G protein (Trussel and Jackson, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have also demonstrated a lack of relationship between cAMP levels and the electrophysiological effects of adenosine [14][15][16][17] , except in forskolin-treated hippocampal slices [18] .…”
Section: Discussionmentioning
confidence: 99%
“…USA 86 (1989) late inositol phospholipid turnover share a common action. They block the inhibitory effects of several receptors coupled to potassium channels via pertussis-toxin-sensitive GTPbinding proteins (10,31). For example, potassium-channel activation elicited by adenosine or serotonin is blocked by these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic stimulation of the inositol phospholipid system in the hippocampus displays a characteristic pharmacology (10,17,18,21). Several muscarinic agonists such as carbachol, oxotremorine M, and oxotremorine 2 possess high efficacy, while others such as oxotremorine, arecoline, and pilocarpine behave as weak partial agonists.…”
Section: Methodsmentioning
confidence: 99%